Observatory of customs controls for Unites States imports : technical standards - Artecona, Raquel (UN ECLAC New YorkUS, 2010)
Presents the extended database of refusals of products at ports of entry into the United States, created by the ECLAC Office in Washington of the number of refusals by country and by product and the reasons for the refusal for the period 2001 - 2008.